2016
DOI: 10.1111/are.13036
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of growth and resistance to Polydora ciliata in the pearl oyster Pinctada fucata

Abstract: The pearl oyster Pinctada fucata is an economically important oyster cultured for pearl production in China. In this study, we used an animal model to estimate the variance components and genetic parameters of growth traits and a sire-dam threshold model to estimate the resistance of P. fucata to polychaete Polydora ciliata. The results showed that the heritability estimates were 0.3850 AE 0.1421 for shell width, 0.3478 AE 0.1292 for body weight and 0.3387 AE 0.1316 for resistance to P. ciliata, and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In Pinctada fuctua , Liu et al. (2017) reported that genetic correlation between shell width and body weight was positive and high (0.883). In C. gigas , Wang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pinctada fuctua , Liu et al. (2017) reported that genetic correlation between shell width and body weight was positive and high (0.883). In C. gigas , Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic correlations between growth traits have been widely reported. In Pinctada fuctua, Liu et al (2017) reported that genetic correlation between shell width and body weight was positive and high (0.883). In C. gigas, Wang et al (2012) identified positive and high (0.76) genetic correlation between SH and SL.…”
Section: Genetic and Phenotypic Correlationsmentioning
confidence: 99%